Plated steel sheet
By forming a rich tissue of Si and Al on the surface of the steel plate and decarbonizing and stabilizing the ferrite phase in high dew point annealing, the problem of LME cracking of the plated steel plate during welding is solved, and the high LME resistance and welding stability are improved.
Patent Information
- Application Number
- CN202380063576.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-06
- Filing Date
- 2023-09-06
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively suppress liquid metal embrittlement (LME) cracking of plated steel plates during welding, resulting in a decrease in weldability.
By forming a large amount of Si and Al structure on the surface of the steel plate and decarburizing during the high dew point annealing process, the ferrite phase is stabilized, thereby covering the surface of the steel plate and inhibiting LME cracking.
It realizes high LME resistance of steel plates, improves welding stability and strength, and is suitable for high-strength steel plate applications.
Smart Images

Figure CN119836483A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a plated steel sheet, and more particularly to a plated steel sheet having high LME resistance. Background Art
[0002] In recent years, the strength of steel sheets used in various fields such as automobiles, home appliances, and building materials has been increasing. For example, in the automotive field, the use of high-strength steel sheets has increased in order to improve fuel efficiency and reduce the weight of the vehicle body.
[0003] In welding of zinc-plated steel sheets, especially high-strength steel sheets, a reduction in weldability due to liquid metal embrittlement (LME) cracking may become a problem, for example, as described in Patent Document 1. LME cracking is believed to occur when the surface layer of the steel sheet transforms into austenite during welding, molten zinc intrudes into the grain boundaries, embrittles the steel sheet, and further tensile stress is applied to the steel sheet during welding.
[0004] Furthermore, as disclosed in Non-Patent Document 1, regarding LME cracking, it is known that the LME sensitivity of the grain boundaries of the ferrite phase is lower than that of the austenite grain boundaries.
[0005] It should be noted that Patent Document 2 discloses a steel plate as a steel plate having improved weldability by suppressing LME cracking, wherein Si oxide particles with a particle size of 20 nm or more are present at a density of 3,000 to 6,000 particles / mm in the surface layer of the steel plate. 2 The number density of the particles is high and they exist in an appropriate particle size distribution.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2019 / 116531
[0009] Patent Document 2: International Publication No. 2020 / 218575
[0010] Non-patent literature
[0011] Non-patent document 1: Influence of the starting microstructure of an advancedhigh strength steel on the characteristics of Zn-Assisted liquid metalembrittlement, D.Bhattacharya et.al., Materials Science and Engineering: A, Vol.804, 2021 Summary of the invention
[0012] Problems to be solved by the invention
[0013] In order to prevent LME cracking, it is effective to suppress the intrusion of Zn and the like contained in the coating into the steel sheet undergoing austenite transformation. There is room for improvement in this regard.
[0014] The present invention has been made in view of such actual conditions, and an object of the present invention is to provide a plated steel sheet having high LME resistance.
[0015] Means used to solve problems
[0016] The present inventors have conducted intensive research on means for solving the above-mentioned problems. As a result, it has been found that by making a steel sheet contain a large amount of Si and Al, forming the steel sheet in an appropriate surface state and performing high dew point annealing, the surface layer of the steel sheet is decarburized, and the ferrite (α) phase is stabilized, and the surface layer of the steel sheet is covered with a ferrite phase with a low C solid solution content, and as a result, LME can be suppressed in a plated steel sheet using the steel sheet.
[0017] The present invention is based on the above-mentioned knowledge and further studies. The gist of the present invention is as follows.
[0018] (1) A plated steel sheet, characterized in that the plated steel sheet has a Zn-containing plating layer on one or both surfaces of a base steel sheet and has a tensile strength of 780 MPa or more, and the chemical composition of the base steel sheet contains, in terms of mass%, the following: C: 0.05-0.40%, Si: 0.7-3.0%, Mn: 0.1-5.0%, sol.Al: 0.7-2.0%, P: 0.0300% or less, S: 0.0300% or less, N: 0.0100% or less, B: 0-0.010%, Ti: 0-0.150%, Nb: 0-0.150%, V: 0-0.150%, Cr: 0-2.00%, Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W: 0-1.00%, Ca: 0-0.10 0%, Mg: 0-0.100%, Zr: 0-0.100%, Hf: 0-0.100%, REM: 0-0.100%, the remainder is Fe and impurities, the total value of Si and sol.Al contents is 1.8% or more, taking the interface between the aforementioned base steel sheet and the aforementioned coating as the starting point, in the depth direction of the aforementioned plated steel sheet, the depth at which the C concentration measured by GDS is 0.05% or less is 10μm or more, taking the interface between the aforementioned base steel sheet and the aforementioned coating as the starting point, in the depth direction of the aforementioned plated steel sheet, the thickness of the layer in which the area ratio of the ferrite phase is 90% or more is 20μm or more, the roughness of the interface between the aforementioned base steel sheet and the aforementioned coating is 3.0μm or less in terms of Ra, the aforementioned coating contains less than 3.0% of Fe in terms of mass%, and the remainder is Zn and impurities.
[0019] (2) The plated steel sheet according to (1) above, wherein the roughness of the interface between the base steel sheet and the plated layer is 2.0 μm or less in terms of Ra.
[0020] (3) The plated steel sheet according to (1) above is characterized in that, starting from the interface between the base steel sheet and the plated layer, the depth at which the C concentration measured by GDS is less than 0.05% in the depth direction of the plated steel sheet is greater than 20 μm.
[0021] (4) The plated steel sheet according to (1) above is characterized in that, starting from the interface between the base steel sheet and the plated layer, the thickness of the layer having an area ratio of ferrite phase of 90% or more in the depth direction of the plated steel sheet is 30 μm or more.
[0022] (5) The plated steel sheet according to any one of (1) to (4) above, wherein the plated layer contains, by mass%, 0 to 30.0% Al and 0 to 10.0% Mg in place of a portion of the Zn.
[0023] (6) The plated steel sheet according to any one of (1) to (4) above, wherein the plated layer contains, by mass%, 10.0 to 30.0% Al and 4.5 to 10.0% Mg in place of a portion of the Zn.
[0024] Effects of the Invention
[0025] According to the present invention, a plated steel sheet having high LME resistance can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a diagram showing a layered ferrite phase formed on the surface layer of the plated steel sheet of the present invention.
[0027] Figure 2 This is a diagram for explaining the LME resistance evaluation in Examples. DETAILED DESCRIPTION
[0028] The present invention will be described below. The present invention is not limited to the following embodiments. First, the outline of improving the LME resistance in the plated steel sheet of the present invention will be described.
[0029] LME cracking occurs because the surface layer of the base steel plate of the plated steel plate is heated during spot welding, causing the steel plate structure of the surface layer to be transformed into austenite, and hot-dip plating invades the steel plate structure along the grain boundaries of austenite, thereby embrittled the grain boundaries. It can be considered that LME cracking occurs because tensile stress is applied to the base steel plate during welding. The plated steel plate of the present invention improves LME resistance by forming a structure on the surface of the base steel plate. It should be noted that in this specification, the surface layer of the base steel plate refers to the range from the outermost surface of the base steel plate to a depth of about 100 μm.
[0030] LME cracking occurs because the surface of the steel plate is heated during spot welding, causing the steel plate structure of the surface to transform into austenite, and hot-dip plating enters the steel plate structure along the grain boundaries of the austenite, thereby embrittled the grain boundaries. It can be considered that LME cracking occurs because tensile stress is applied to the steel plate during welding. The steel plate of the present invention improves LME resistance by forming a structure on the surface of the steel plate. It should be noted that in this specification, the surface layer of the steel plate refers to the range from the outermost surface of the steel plate to a depth of about 100 μm.
[0031] However, it is considered that even when the C concentration in the surface layer of the steel sheet is low, if there is a lot of austenite (γ) with high LME sensitivity in the structure of the surface layer, the LME resistance may be reduced. Therefore, in the steel sheet of the present embodiment, the thickness of the layer having an area ratio of ferrite phase of 90% or more is 20 μm or more in the depth direction from the interface between the base steel sheet and the coating layer. In addition, the plated steel sheet of the present invention contains a large amount of Si, which has been known to reduce the LME resistance if contained in the steel sheet. This is because the present inventors conducted research and found that, contrary to the existing understanding, by containing a large amount of Si and sol.Al together, the LME resistance is improved.
[0032] In the present invention, a strong strain is imparted to the surface layer without increasing the surface roughness of the steel sheet, and the steel sheet is annealed at a high dew point. As a result, oxygen can be diffused into the steel sheet to form internal oxides, thereby suppressing the formation of external oxides. This is because it is believed that the C concentration in the surface layer of the steel sheet can be reduced, and the ferrite can be stabilized by the effect of the combined addition of Si and Al.
[0033] That is, the plated steel sheet of the present invention utilizes the combined effects of high Si and sol.Al contents, imparting strain to the surface layer before annealing, and controlling the dew point during annealing to form a layer with a low C concentration and a high ferrite area ratio on the surface layer of the steel sheet, thereby making it possible to improve LME resistance.
[0034] Hereinafter, the present invention will be described in detail.
[0035] First, the chemical composition of the base steel sheet is described. Hereinafter, "%" in the chemical composition means "mass %". In addition, in the numerical range of the chemical composition, the numerical range represented by "to" means a range including the numerical values recorded before and after "to" as the lower limit and the upper limit.
[0036] (C: 0.05~0.40%)
[0037] C (carbon) is an element that ensures the strength of steel. In order to obtain a tensile strength of 780 MPa or more, which is the object of the present invention, the C content is set to 0.05-0.40% in consideration of the balance with weldability, and in order to prevent the C concentration of the surface layer of the base steel plate from being excessively increased. When the C content is too high, the C concentration of the surface layer does not decrease, and the ferrite fraction does not increase even through the high dew point annealing described later. The C content may be 0.07% or more, 0.10% or more, or 0.12% or more. The C content may be 0.35% or less, 0.30% or less, or 0.25% or less.
[0038] (Si: 0.7~3.0%, sol.Al: 0.7~2.0%, Si+sol.Al≥1.8%)
[0039] Si (silicon) is an element that promotes ferrite stabilization and decarburization by being added in combination with Al (aluminum). In order to obtain such an effect of improving LME resistance, Si: 0.7-3.0%, sol.Al: 0.7-2.0%, and the total content of Si and sol.Al is set to 1.8% or more. This is because by making the contents of Si and sol.Al satisfy such a numerical range, decarburization of the surface layer of the steel plate can be promoted in the heat treatment of the manufacturing process of the steel plate of this embodiment, and the ferrite of the surface layer can be stabilized. Sol.Al represents acid-soluble Al that is soluble in acid without forming oxides such as Al2O3, and is obtained as Al measured by subtracting the insoluble residue on the filter paper generated during the analysis of Al. The content of Si can be 0.8% or more, 0.9% or more, or 1.0% or more. The content of Si can be 2.8% or less, 2.5% or less, or 2.0% or less. The content of sol.Al can be 0.8% or more, 0.9% or more, or 1.0% or more. The content of sol.Al may be 1.8% or less, 1.6% or less, or 1.5% or less. The total content of Si and sol.Al may be 1.9% or more, or 2.0% or more.
[0040] (Mn: 0.1~5.0%)
[0041] Mn (manganese) is an element effective in improving the strength of steel by obtaining a hard structure. Considering the balance between the strength of steel and the reduction in workability caused by Mn segregation, the Mn content is set to 0.1-5.0%. The Mn content may be 0.5% or more, 1.0% or more, or 1.5% or more. The Mn content may be 4.5% or less, 4.0% or less, or 3.5% or less.
[0042] (P: 0.0300% or less)
[0043] P (phosphorus) is an impurity generally contained in steel. When the content of P is greater than 0.0300%, there is a risk of reduced weldability. Therefore, the content of P is set to 0.0300% or less. The content of P may be less than 0.0200%, less than 0.0100%, or less than 0.0050%. P is preferably not contained, and the lower limit of the content of P is 0%. From the perspective of dephosphorization cost, the content of P may be greater than 0%, 0.0001% or more, or 0.0005% or more.
[0044] (S: 0.0300% or less)
[0045] S (sulfur) is an impurity generally contained in steel. When the S content is greater than 0.0300%, weldability decreases, and further, there is a risk that the amount of MnS precipitation increases and workability such as bendability decreases. Therefore, the S content is set to 0.0300% or less. The S content may be less than 0.0100%, less than 0.0050%, less than 0.0030%, less than 0.0020% or less than 0.0010%. S is preferably not contained, and the lower limit of the S content is 0%. From the perspective of desulfurization cost, the S content may be greater than 0%, 0.0001% or more, or 0.0005% or more.
[0046] (N: 0.0100% or less)
[0047] N (nitrogen) is an impurity generally contained in steel. When the N content is greater than 0.0100%, there is a risk of reduced weldability. Therefore, the N content is set to 0.0100% or less. The N content may be less than 0.0080%, less than 0.0050%, less than 0.0030%, less than 0.0020%, or less than 0.0010%. N is preferably not contained, and the lower limit of the N content is 0%. From the perspective of manufacturing cost, the N content may be greater than 0%, 0.0001% or more, 0.0002% or more, 0.0003% or more, or 0.0005% or more.
[0048] (B: 0~0.010%)
[0049] B (boron) is an element that helps to improve strength by improving hardenability. In addition, it segregates at grain boundaries to strengthen grain boundaries and improve toughness, so it can be contained as needed. Since it is not an essential element, the lower limit of the content of B is 0%. This effect can be obtained even if it is contained in trace amounts. When contained, the content of B is preferably 0.0001% or more. The content of B can be 0.0002% or more, 0.0003% or more, 0.0005% or more, 0.0007% or more, or 0.0010% or more. On the other hand, from the perspective of ensuring sufficient toughness, the content of B is set to less than 0.010%. The content of B can be less than 0.0080%, less than 0.0060%, less than 0.0050%, less than 0.0040%, or less than 0.0030%.
[0050] (Ti: 0~0.150%)
[0051] Ti (titanium) is an element that precipitates as TiC during the cooling of steel and helps to improve strength, so it can be contained as needed. Since it is not an essential element, the lower limit of the Ti content is 0%. This effect can be obtained even if it is contained in a trace amount, and the Ti content when contained is preferably 0.0001% or more. The Ti content can be 0.0002% or more, 0.0003% or more, 0.0005% or more, 0.0007% or more, or 0.0010% or more. On the other hand, when contained in excess, there is a risk of generating coarse TiN and damaging toughness, so the Ti content is set to 0.150% or less. The Ti content can be 0.1000% or less, 0.0500% or less, 0.0300% or less, 0.0200% or less, 0.0100% or less, 0.0050% or less, or 0.0030% or less.
[0052] (Nb: 0~0.150%)
[0053] Nb (niobium) is an element that helps to improve strength by improving hardenability, so it can be contained as needed. Since it is not an essential element, the lower limit of the Nb content is 0%. This effect can be obtained even if it is contained in a trace amount, and the Nb content when contained is preferably 0.001% or more. The Nb content can be 0.002% or more, 0.003% or more, 0.005% or more, or 0.008% or more. On the other hand, from the perspective of ensuring sufficient toughness, the Nb content is set to 0.150% or less. The Nb content can be 0.100% or less, 0.060% or less, 0.050% or less, 0.040% or less, or 0.030% or less.
[0054] (V: 0~0.150%)
[0055] V (vanadium) is an element that helps to improve strength by improving hardenability, so it can be contained as needed. Since it is not an essential element, the lower limit of the V content is 0%. This effect can be obtained even if it is contained in a trace amount, and the V content when contained is preferably 0.001% or more. The V content can be more than 0.002%, more than 0.003% or more than 0.005%. On the other hand, from the perspective of ensuring sufficient toughness, the V content is set to less than 0.150%. The V content can be less than 0.100%, less than 0.060%, less than 0.050%, less than 0.040%, less than 0.030% or less than 0.020%.
[0056] (Cr: 0~2.00%)
[0057] Cr (chromium) is effective in improving the hardenability of steel and the strength of steel, so it can be contained as needed. Since it is not an essential element, the lower limit of the Cr content is 0%. This effect can be obtained even if it is contained in a trace amount, and the Cr content when contained is preferably set to more than 0.001%. The Cr content can be more than 0.01%, more than 0.02%, more than 0.03%, more than 0.05% or more than 0.08%. On the other hand, when contained in excess, a large amount of Cr carbides are formed, which may damage the hardenability, so the Cr content is set to less than 2.00%. The Cr content can be less than 1.80%, less than 1.50%, less than 1.20%, less than 1.00%, less than 0.70%, less than 0.50% or less than 0.30%.
[0058] (Ni: 0~2.00%)
[0059] Ni (nickel) is effective for improving the hardenability of steel and the strength of steel, so it can be contained as needed. Since it is not an essential element, the lower limit of the content of Ni is 0%. This effect can be obtained even if it is contained in a trace amount, and the content of Ni when contained is preferably more than 0.001%. The content of Ni can be more than 0.01% or more than 0.02%. On the other hand, excessive addition of Ni will increase the cost, so the content of Ni is set to less than 2.00%. The content of Ni can be less than 1.80%, less than 1.50%, less than 1.20%, less than 1.00%, less than 0.80%, less than 0.50%, less than 0.30%, less than 0.20%, less than 0.10% or less than 0.05%.
[0060] (Cu: 0-2.00%)
[0061] Cu (copper) is effective for improving the hardenability of steel and the strength of steel, so it can be contained as needed. Since it is not an essential element, the lower limit of the content of Cu is 0%. This effect can be obtained even if it is contained in a trace amount, and the content of Cu when contained is preferably 0.0001% or more. The content of Cu can be more than 0.0002%, more than 0.0003% or more than 0.0005%. On the other hand, from the perspective of suppressing the reduction of toughness and the cracking of the slab after casting, the content of Cu is set to less than 2.00%. The content of Cu can be less than 1.8000%, less than 1.5000%, less than 1.2000%, less than 1.0000%, less than 0.5000%, less than 0.1000%, less than 0.0500%, less than 0.0100%, less than 0.0050%, less than 0.0030% or less than 0.0020%.
[0062] (Mo: 0~1.00%)
[0063] Mo (molybdenum) is effective in improving the hardenability of steel and the strength of steel, so it can be contained as needed. Since it is not an essential element, the lower limit of the Mo content is 0%. This effect can be obtained even if it is contained in a trace amount, and the Mo content when contained is preferably 0.001% or more. The Mo content can be more than 0.01%, more than 0.02%, more than 0.03%, more than 0.05% or more than 0.08%. On the other hand, from the perspective of suppressing the reduction of toughness, the Mo content is set to less than 1.00%. The Mo content can be less than 0.90%, less than 0.70%, less than 0.50% or less than 0.30%.
[0064] (W: 0~1.00%)
[0065] W (tungsten) is effective in improving the hardenability of steel and the strength of steel, so it can be contained as needed. Since it is not an essential element, the lower limit of the content of W is 0%. This effect can be obtained even if it is contained in a trace amount, and the content of W when contained is preferably 0.001% or more. The content of W can be more than 0.002%, more than 0.005% or more than 0.01%. On the other hand, from the perspective of suppressing the reduction of toughness, the content of W is set to less than 1.00%. The content of W can be less than 0.90%, less than 0.70%, less than 0.50%, less than 0.30%, less than 0.10%, less than 0.05% or less than 0.03%.
[0066] (Ca: 0~0.100%)
[0067] Ca (calcium) is an element that helps control inclusions, especially fine dispersion of inclusions, and has the effect of improving toughness, so it can be contained as needed. Since it is not an essential element, the lower limit of the Ca content is 0%. This effect can be obtained even if it is contained in trace amounts, and the Ca content when contained is preferably 0.0001% or more. The Ca content can be 0.0002% or more. On the other hand, when contained in excess, the deterioration of the surface properties sometimes becomes obvious, so the Ca content is set to 0.100% or less. The Ca content can be 0.0800% or less, 0.0500% or less, 0.0100% or less, 0.0050% or less, 0.0030% or less, 0.0020% or less, 0.0010% or less, 0.0008% or less, or 0.0005% or less.
[0068] (Mg: 0~0.100%)
[0069] Mg (magnesium) is an element that helps control inclusions, especially fine dispersion of inclusions, and has the effect of improving toughness, so it can be contained as needed. Since it is not an essential element, the lower limit of the Mg content is 0%. This effect can be obtained even if it is contained in trace amounts, and the Mg content when contained is preferably 0.0001% or more. The Mg content can be 0.0002% or more, 0.0003% or more, 0.0005% or more, or 0.0008% or more. On the other hand, when excessively contained, the deterioration of the surface properties sometimes becomes obvious, so the Mg content is set to 0.100% or less. The Mg content can be 0.090% or less, 0.080% or less, 0.050% or less, 0.010% or less, 0.005% or less, or 0.003% or less.
[0070] (Zr: 0~0.100%)
[0071] Zr (zirconium) is an element that helps control inclusions, especially fine dispersion of inclusions, and has the effect of improving toughness, so it can be contained as needed. Since it is not an essential element, the lower limit of the Zr content is 0%. This effect can be obtained even if it is contained in trace amounts, and the Zr content when contained is preferably 0.001% or more. The Zr content can be more than 0.002%, more than 0.003%, more than 0.005%, or more than 0.010%. On the other hand, when contained in excess, the deterioration of the surface properties sometimes becomes obvious, so the Zr content is set to less than 0.100%. The Zr content can be less than 0.080%, less than 0.050%, less than 0.040%, or less than 0.030%.
[0072] (Hf: 0~0.100%)
[0073] Hf (Hafnium) is an element that helps control inclusions, especially fine dispersion of inclusions, and has the effect of improving toughness, so it can be contained as needed. Since it is not an essential element, the lower limit of the Hf content is 0%. This effect can be obtained even if it is contained in a trace amount, and the Hf content when contained is preferably 0.0001% or more. The Hf content can be more than 0.0002%, more than 0.0003%, more than 0.0005%, or more than 0.0008%. On the other hand, when contained in excess, the deterioration of the surface properties sometimes becomes obvious, so the Hf content is set to less than 0.100%. The Hf content can be less than 0.050%, less than 0.030%, less than 0.010%, less than 0.005%, or less than 0.003%.
[0074] REM: 0~0.100%
[0075] REM (rare earth element) is an element that helps to control inclusions, especially fine dispersion of inclusions, and has the effect of improving toughness, so it can be contained as needed. Since it is not an essential element, the lower limit of the REM content is 0%. This effect can be obtained even if it is contained in a trace amount, and the REM content when contained is preferably 0.0001% or more. The REM content can be 0.0003% or more or 0.0005% or more. On the other hand, when contained in excess, the deterioration of surface properties sometimes becomes obvious, so the REM content is set to 0.100% or less. The REM content can be 0.0500% or less, 0.0300% or less, 0.0100% or less, 0.0050% or less, 0.0030% or less, or 0.0020% or less. It should be noted that REM is the abbreviation of Rare Earth Metal, which refers to an element belonging to the lanthanide series. REM is usually added in the form of a mixed rare earth alloy.
[0076] In the plated steel sheet of the present invention, the remainder other than the above chemical components is formed of Fe and impurities. Here, impurities refer to components mixed in due to various main reasons in the manufacturing process, including raw materials such as ore and scrap, when the steel sheet is manufactured industrially, and refer to components contained in a range that does not adversely affect the LME resistance of the plated steel sheet of the present invention and can obtain the LME resistance required by the plated steel sheet of the present invention.
[0077] The chemical composition of the base steel sheet can be analyzed by an elemental analysis method known to those skilled in the art, for example, by inductively coupled plasma mass spectrometry (ICP-MS). However, for C and S, a combustion-infrared absorption method can be used, and for N, an inert gas fusion-thermal conductivity method can be used for measurement. These analyses can be performed using a sample obtained from the base steel sheet according to a method based on JIS G0417:1999.
[0078] Next, the surface layer portion of the base steel sheet will be described.
[0079] [C concentration]
[0080] In the plated steel sheet of the present invention, the depth where the C concentration measured by GDS (glow discharge emission spectroscopy) is 0.05% or less is 10 μm or more in the depth direction from the surface of the base steel sheet. Here, the starting point in the depth direction is the interface between the plated layer and the base steel sheet.
[0081] The sensitivity to LME decreases if the C concentration decreases, so the LME resistance is improved by reducing the C concentration in the surface layer. In addition, since C is an austenite stabilizing element, the ferrite phase with low LME sensitivity described later can be stabilized by reducing the C concentration.
[0082] Such a surface structure can be obtained by making the chemical composition of the steel sheet contain a large amount of Si and Al as described above, and by the heat treatment described later.
[0083] If the depth at which the C concentration is 0.05% or less is 10 μm or more, the effect of improving LME resistance can be obtained, so the upper limit of the depth is not particularly limited. For example, it may be 50 μm or less, 40 μm or less, or 30 μm or less. The depth at which the C concentration is 0.05% or less is preferably 20 μm or more.
[0084] GDS measurement was performed 5 times along the thickness direction, and the average value was taken as the C concentration. The measurement conditions were as follows. The starting point of "depth" was the interface between the base steel plate and the coating. The interface between the base steel plate and the coating was set to the position where the Fe concentration measured by GDS measurement reached 93% of the Fe concentration at a depth of 150 μm.
[0085] Equipment: High-frequency glow discharge emission spectrometer (manufactured by LECO JAPAN CORPORATION, model "GDS850A"
[0086] Ar gas pressure: 0.3MPa
[0087] Anode diameter: 4mmφ
[0088] RF output power: 30W
[0089] Measuring time: 200 to 1500 seconds
[0090] [Ferrite phase]
[0091] In the plated steel sheet of the present invention, the thickness of the layer having a ferrite phase area ratio of 90% or more in the depth direction from the surface of the base steel sheet is 20 μm or more. Here, the starting point in the depth direction is the interface between the plated layer and the base steel sheet. Figure 1An example of a structure photograph of the vicinity of the surface layer of the plated steel sheet of the present invention by SEM is shown. Figure 1 It is a cross section of the plated steel sheet in the thickness direction, and the upper side of the drawing is the surface of the plated steel sheet. Figure 1 The surface layer of the steel sheet in the embodiment includes a layer having a low C concentration and an area ratio of ferrite (α) phase of 90% or more. The inside of the base steel sheet is a structure mainly composed of martensite (M) and also containing ferrite. Figure 1 In the plated steel sheet, a layer having an area ratio of ferrite phase of 90% or more exists in a thickness of 40 μm in the surface layer of the base steel sheet.
[0092] It is known that the LME sensitivity of the grain boundary of the ferrite phase is lower than that of the γ (austenite) grain boundary (for example, Non-Patent Document 1). Therefore, by having a thick structure mainly composed of the ferrite phase in the surface layer of the base steel sheet, LME becomes less likely to occur even when the plating is melted, and the LME resistance can be improved. Such a surface structure can be obtained by making the chemical composition of the steel sheet contain a large amount of Si and Al as described above, and by the heat treatment described later.
[0093] If the thickness of the region where the area ratio of the ferrite phase is 90% or more reaches 20 μm or more, the effect of improving LME resistance can be obtained, so the upper limit of the thickness is not particularly limited. The thickness may be, for example, 100 μm or less, 80 μm or less, or 60 μm or less. The thickness of the region where the area ratio of the ferrite phase is 90% or more may be 30 μm or more.
[0094] The thickness of the region where the area ratio of the ferrite phase is 90% or more can be determined by etching the L section of the base steel plate with nitric acid, and observing with an SEM to distinguish martensite, bainite, and ferrite based on their organizational morphology. Specifically, the L-direction section is ground, mirror-polished, and then etched with nitric acid to reveal the steel structure. Then, secondary electron images of 5 fields of view are taken at equal intervals at a magnification of 1500 times within a range of 500 μm in the depth direction relative to the steel surface. The area ratio of the ferrite phase is measured by the point counting method (according to ASTM E562), and the thickness of the region where the area ratio of the ferrite phase is 90% or more is measured for each photographed field of view.
[0095] Here, the area ratio of the ferrite phase refers to the area ratio obtained by observing the L cross section. In the middle of the thickness direction, when the C cross section is partially observed, even if there is a place where the area ratio of the ferrite phase is less than 90%, there is no problem as long as the area ratio of the ferrite phase in the L cross section to a depth of 20 μm is 90% or more. More specific area ratios are as follows.
[0096] The ferrite area ratio is measured as follows. A cross section of the base steel plate in the plate thickness direction perpendicular to the rolling direction is cut out, and after mirror polishing, the steel structure is exposed using nitric acid ethanol solution, and a secondary electron image is taken using a field emission scanning electron microscope. The range of the observed field of view is set to the range from the interface between the base steel plate and the coating to 500μm in the depth direction, and 5 fields of view are observed at equal intervals. For the obtained tissue photograph, the score of each tissue is calculated by the point counting method. First, draw equally spaced grids on the tissue photograph. Next, determine which of the tempered martensite, pearlite, ferrite, primary martensite or retained austenite, bainite the structure at each grid point belongs to. The number of grid points belonging to each structure is calculated and divided by the total number of grid points, thereby determining the score of each structure. In the present invention, the grid spacing is set to 2μm×2μm, and the total number of grid points is set to 1500 points.
[0097] The judgment criteria of pearlite, ferrite, martensite and bainite are as follows. The region with lower structure (lath boundary, lath block boundary) in the grain and multiple variants of carbide precipitation is judged as tempered martensite. In addition, the region where cementite is precipitated in layers is judged as pearlite. The region where the brightness is small and the lower structure cannot be confirmed is judged as ferrite. The region where the brightness is large and the lower structure is not shown by etching is judged as primary martensite or retained austenite. The region not belonging to any of the above is judged as bainite. In short, as long as ferrite is distinguished from the structure other than it, the area ratio of ferrite phase can be obtained.
[0098] [Plating]
[0099] The plated steel sheet of the present invention has a plated layer on the above-mentioned base steel sheet. The plated layer may be formed on one side or both sides of the base steel sheet.
[0100] [Chemical composition of the coating]
[0101] The chemical composition of the plating is described. "%" related to the content of an element means "mass %" unless otherwise stated. In the numerical range of the chemical composition of the plating layer, the numerical range represented by "to" indicates a range including the numerical values recorded before and after "to" as the lower limit and upper limit unless otherwise specified.
[0102] (Fe: 3.0% or less)
[0103] Fe is not included in the plating bath, but can be included in the plating layer by diffusion from the base steel sheet when the plated steel sheet is heat-treated after forming the plating layer containing Zn on the base steel sheet. Therefore, Fe is not included in the plating layer in the state without heat treatment, and the Fe content can be 0%. In addition, the Fe content can be 3.0% or less, for example, 2.0% or less, or 1.0% or less.
[0104] The remainder of the coating layer other than the above components is formed of Zn and impurities. Impurities in the coating layer refer to components that are mixed into the coating layer due to various main reasons in the manufacturing process, including raw materials, when the coating layer is manufactured, and are not intentionally added to the coating layer. In the coating layer, a trace amount of elements other than the basic components and optional additional components described above may be contained as impurities within a range that does not hinder the effect of the present invention.
[0105] The plating layer may contain Al: 0 to 30.0% and Mg: 0 to 10.0% in place of a part of the aforementioned Zn.
[0106] (Al: 0-30.0%)
[0107] Since Al is an element that improves the corrosion resistance of the coating by being included together with Zn, it can be contained as needed. Therefore, the content of Al can be 0%. In order to form a coating containing Zn and Al, it is preferred that the content of Al can be 0.01% or more, for example, it can be 1.0% or more, 3.0% or more, 5.0% or more, 10.0% or more, or 15.0% or more. When the content of Al is too much, the effect of improving the corrosion resistance will be saturated, so the content of Al can be 30.0% or less, for example, it can be 25.0% or less, 20.0% or less.
[0108] (Mg: 0~10.0%)
[0109] Mg is an element that improves the corrosion resistance of the coating by being included together with Zn and Al, so it can be contained as needed. Therefore, the content of Mg can be 0%. In order to form a coating containing Zn, Al and Mg, it is preferred that the content of Mg can be 0.01% or more, for example, it can be 1.0% or more, 2.0% or more, 3.0% or more, 4.5% or more, or 5.0% or more. When the content of Mg is too much, poor appearance or non-plating may occur, so the content of Mg can be 10.0% or less, for example, 8.0% or less, or 6.0% or less.
[0110] The chemical composition of the coating can be determined by dissolving the coating in an acid solution to which an inhibitor for inhibiting corrosion of the base steel sheet is added, and measuring the resulting solution by ICP (high frequency inductively coupled plasma) spectroscopy. The acid solution to which the inhibitor is added can be, for example, a 10 mass % hydrochloric acid solution to which 0.06 mass % of an inhibitor (IBIT manufactured by Asahi Chemical Industry Co., Ltd.) is added.
[0111] The thickness of the plating layer may be, for example, 3 to 50 μm. The amount of the plating layer applied is not particularly limited, but may be, for example, 10 to 170 g / m per single side. 2In the present invention, the coating adhesion amount is determined by dissolving the coating in an acid solution to which an inhibitor for inhibiting corrosion of the base steel sheet is added, and by the weight change of the coating before and after pickling and stripping. The coating thickness may be 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more. The coating thickness may be 40 μm or less, or 30 μm or less. The coating adhesion amount may be 20 g / m per single side. 2 Above, 30g / m 2 Above, 40g / m 2 Above or 50g / m 2 The coating weight can be 150g / m per side. 2 Below, 130g / m 2 Below, 120g / m 2 Below or 100g / m 2 the following.
[0112] [Interface roughness]
[0113] The roughness of the interface between the coating layer of the plated steel sheet of the present invention and the base steel sheet is 3.0 μm or less according to the arithmetic mean roughness Ra defined in JIS B0601:2013. When the roughness increases, cracking becomes more likely to occur due to stress concentration, so the LME resistance decreases. The roughness of the interface can be the surface roughness of the base steel sheet measured by removing the coating. Considering the adhesion of the coating, Ra can be 2.5 μm or less or 2.0 μm or less.
[0114] [Tensile strength]
[0115] Since the present invention suppresses the occurrence of LME in high-strength steel sheets, the plated steel sheet of the present invention is high-strength. Specifically, it has a tensile strength of 780 MPa or more. The upper limit of the tensile strength is not particularly limited, and from the perspective of ensuring toughness, for example, it can be 2000 MPa or less. The tensile strength is measured by obtaining a JIS No. 5 tensile test piece with the direction perpendicular to the rolling direction as the longitudinal direction, and performing it in accordance with JIS Z2241: 2011. The tensile strength can be 880 MPa or more, 980 MPa or more, 1080 MPa or more, or 1180 MPa or more. The tensile strength can be 1900 MPa or less, or 1800 MPa or less.
[0116] The plate thickness of the plated steel sheet of the present invention is not particularly limited. For example, it can be set to 0.6 to 3.2 mm. The plate thickness can be 0.8 mm or more or 1.0 mm or more. The plate thickness can be 3.0 mm or less, 2.6 mm or less, 2.4 mm or less, 2.2 mm or less, 2.0 mm or less, or 1.8 mm or less.
[0117] Next, the method for producing the plated steel sheet of the present invention will be described.
[0118] The plated steel sheet of the present invention can be obtained, for example, by a manufacturing method comprising the following steps: a casting step of casting molten steel with adjusted chemical composition to form a steel sheet, a hot rolling step of hot rolling the steel sheet to obtain a hot-rolled steel sheet, a coiling step of coiling the hot-rolled steel sheet, a cold rolling step of cold-rolling the coiled hot-rolled steel sheet to obtain a cold-rolled steel sheet, a pre-treatment step of brushing the cold-rolled steel sheet, an annealing step of annealing the pre-treated cold-rolled steel sheet, and a plating step of plating the annealed cold-rolled steel sheet. Alternatively, after the hot rolling step, pickling may be performed without coiling and cold rolling may be performed directly.
[0119] [Casting process]
[0120] The conditions of the casting process are not particularly limited. For example, various secondary smeltings may be performed after melting in a blast furnace, an electric furnace, etc., and then casting may be performed by a conventional continuous casting, a casting method by an ingot casting method, or the like.
[0121] [Hot rolling process]
[0122] Hot-rolled steel sheets can be obtained by hot rolling the steel sheets obtained by casting. The hot rolling process is performed by directly hot rolling the cast steel sheets or by cooling them first and then reheating and hot rolling them. In the case of reheating, the heating temperature of the steel sheets can be, for example, 1100 to 1250°C. In the hot rolling process, rough rolling and finish rolling are usually performed. The temperature and reduction ratio of each rolling can be appropriately changed according to the desired metal structure and plate thickness. For example, the end temperature of the finish rolling can be 900 to 1050°C, and the reduction ratio of the finish rolling can be 10 to 50%.
[0123] [Coiling process]
[0124] The hot rolled steel sheet can be coiled at a predetermined temperature. The coiling temperature can be appropriately changed according to the desired metal structure, for example, 500 to 800°C. The hot rolled steel sheet can be subjected to a predetermined heat treatment before coiling or after coiling. Alternatively, pickling can be performed after the hot rolling process without coiling and cold rolling can be performed as described below.
[0125] [Cold rolling process]
[0126] After pickling the hot-rolled steel sheet, the hot-rolled steel sheet can be cold-rolled to obtain a cold-rolled steel sheet. The cold-rolling reduction ratio can be appropriately changed according to the desired metal structure and plate thickness, for example, 20 to 80%. After the cold-rolling process, the steel sheet can be cooled to room temperature by air cooling, for example.
[0127] [Pre-treatment process]
[0128] As described above, in the surface layer of the steel plate, in the depth direction, the thickness of the layer in which the area ratio of the ferrite phase is 90% or more is set to be 20 μm or more. In order to make the depth in the depth direction where the C concentration is 0.05% or less in the GDS measurement to be 10 μm or more, it is necessary to perform a prescribed pretreatment and then anneal.
[0129] The pretreatment includes grinding the surface of the cold-rolled steel sheet with a grinding brush (brushing treatment). As a grinding brush that can be used, for example, M-33 manufactured by HOTANI Co., Ltd. can be cited. In this way, strain can be introduced without increasing the roughness of the surface. During grinding, a 1.0-5.0% aqueous solution of NaOH can be applied to the surface of the steel sheet. The brush pressure can be 0.5-10.0 mm, and the rotation speed can be 100-1000 rpm. By controlling the brushing treatment to such coating liquid conditions, brush pressure, and rotation speed, decarburization can be promoted in the annealing process described later, and a ferrite-stabilized structure can be efficiently formed on the surface of the steel sheet.
[0130] [Annealing process]
[0131] After the pretreatment process, the cold-rolled steel sheet is annealed. Annealing is performed under a tension of 1 to 20 MPa. If tension is applied during annealing, strain can be more effectively introduced into the steel sheet, promoting decarburization of the surface layer.
[0132] The holding temperature of the annealing process is set to 750-900°C. The holding temperature may be 770-870°C. By setting it in such a range, decarburization can be promoted, the C concentration of the surface layer can be reduced, and the ferrite phase can be stabilized. The heating rate to the holding temperature is not particularly limited, and it can be carried out at 1-10°C / second.
[0133] The holding time at the holding temperature in the annealing step is set to 20 to 300 seconds. The holding time may be 30 to 250 seconds. By setting the holding time in such a range, decarburization can be promoted, the C concentration in the surface layer can be reduced, and the ferrite phase can be stabilized.
[0134] The atmosphere of the annealing process is set to a dew point of -30 to 20°C. The dew point can be -10 to 5°C. The atmosphere can be, for example, N2-1 to 10 vol% H2, N2-2 to 4 vol% H2. If the dew point is too high or too low, a phase containing oxides such as Si, Mn, and Al is formed on the outside of the steel sheet, and decarburization is no longer promoted. Furthermore, the mutual diffusion of the plating component and the steel component may be hindered, and the plating property may become insufficient.
[0135] According to the production method including the above steps, a steel sheet in which decarburization is promoted in the surface layer of the steel sheet and the ferrite phase is stabilized can be obtained.
[0136] [Plating process]
[0137] Next, the cold-rolled steel sheet after annealing is plated. The plating treatment can be carried out according to methods known to those skilled in the art. The plating treatment can be carried out, for example, by hot-dip plating or by electroplating. Preferably, the plating treatment is carried out by hot-dip plating. The conditions of the plating treatment can be appropriately set in consideration of the chemical composition, thickness and adhesion amount of the desired coating. For example, it can be immersed in a hot-dip galvanizing bath at 420 to 480°C with adjusted chemical composition for 1 to 10 seconds, and then pulled out at 20 to 200 mm / second after dipping, and the coating adhesion amount can be controlled by using N2 wiping gas.
[0138] The plated steel sheet of the present invention is high in strength and has high LME resistance, so it can be suitably used in a wide range of fields such as automobiles, home appliances, and building materials. It is particularly preferably used in the automotive field. Plated steel sheets for automotive use are often spot welded, in which case LME cracking becomes a significant problem. Therefore, when the plated steel sheet of the present invention is used as a steel sheet for automobiles, the effect of the present invention of having high LME resistance can be suitably exerted.
[0139] Furthermore, the plated steel sheet of the present invention is also excellent in corrosion resistance due to the formation of a thick decarburized layer in the surface layer, and is therefore suitable for the automotive field in this respect as well.
[0140] Example
[0141] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0142] 《Example A》
[0143] First, the preliminary experiment conducted by the inventors when the present invention was obtained is described. Steel plates (plate thickness 1.2 mm) with changed Si and Al contents were spot welded with conventional alloyed hot-dip galvanized steel plates (plate thickness 1.6 mm) under the conditions shown in Table 1, and LME cracking during spot welding was confirmed. Table 2 shows the results. As shown in Table 2, it was confirmed that LME was suppressed by high Si-high Al steel.
[0144] Table 1
[0145]
[0146] Table 2
[0147]
[0148] Embodiment B
[0149] (Preparation of Steel Plate Samples)
[0150] <Example 1>
[0151] Molten steel adjusted to the chemical composition described in No. 1 of Table 3 was melted in a blast furnace and cast by continuous casting to obtain a steel sheet. The obtained steel sheet was heated to 1200°C, and hot rolled with the finishing temperature of the finish rolling set to 950°C and the reduction rate of the finish rolling set to 30%, thereby obtaining a hot-rolled steel sheet. The obtained hot-rolled steel sheet was coiled at a coiling temperature of 650°C, pickled, and then cold rolled at a reduction rate of 50%, thereby obtaining a cold-rolled steel sheet. The thickness of the cold-rolled steel sheet was set to 1.6 mm.
[0152] Next, a 2.0% NaOH aqueous solution was applied to the cold-rolled steel sheet and subjected to brushing treatment. The brushing was performed using M-33 manufactured by HOTANI Co., Ltd. as a grinding brush at a brush reduction of 2.0 mm and a rotation speed of 600 rpm (Condition A in Table 4).
[0153] After the pretreatment step and before the annealing step, the surface roughness of the steel sheet was measured according to JIS B 0601: 2013. That is, 10 locations were randomly selected on the surface of the surface layer side, and the surface profile was measured at each location using a contact surface roughness meter, and the arithmetic average roughness Ra obtained by arithmetically averaging the surface roughness of these locations was evaluated as follows.
[0154] Evaluation AA: 2.0μm or less
[0155] Evaluation A: more than 2.0 μm and 3.0 μm or less
[0156] Evaluation B: more than 3.0 μm
[0157] Then, the steel plate samples were annealed in a furnace with an oxygen concentration of 20 ppm or less in an N2-4% H2 gas atmosphere at a dew point of 0°C, a holding temperature of 800°C, and a holding time of 100 seconds. For all steel plate samples, the heating rate during annealing was 6.0°C / second up to 500°C and 2.0°C / second from 500°C to the holding temperature. The annealing was performed under a tension of 15 MPa.
[0158] After annealing, the plated steel sheet was subjected to plating treatment. The plated steel sheet was immersed in a hot-dip galvanizing bath (Zn-0.2% Al) at 460°C for 3 seconds, and then pulled out at 100 mm / s. The coating weight was controlled to 50 g / m by using N2 wiping gas. 2 .
[0159] <Examples 2 to 28, Comparative Examples 29 to 41>
[0160] The plated steel sheet was manufactured in the same manner as in Example 1 except that the chemical composition was as described in Table 3 and the conditions of the pretreatment process, annealing process, and plating process were as described in Table 4. It should be noted that the pretreatment of brushing was omitted in No. 40. In addition, No. 41 used D-100 manufactured by HOTANI Co., Ltd. as a grinding brush (Condition B in Table 4). D-100 is a brush with a grinding amount about twice that of M-33. The composition and bath temperature of the plating species shown in Table 4 are as follows.
[0161] A: Zn-0.2%Al (460℃)
[0162] B: Zn-0.5%Al (440℃)
[0163] C: Zn-1.5%Al-1.5%Mg (500℃)
[0164] D: Zn-20%Al-7%Mg (530℃)
[0165] E: Zn-30%Al-10%Mg (530℃)
[0166] Table 3
[0167]
[0168] ※ The underlined elements are outside the scope of the present invention.
[0169] Table 4
[0170]
[0171] ※ The underlined part is outside the range of the preferred manufacturing method. (Surface structure evaluation)
[0172] A sample cut into 30 mm × 30 mm was obtained from the obtained plated steel sheet, and GDS measurement was performed 5 times along the plate thickness direction under the above-mentioned conditions to determine the depth at which the C concentration was 0.05% or less, which is shown in "C ≤ 0.05% depth" in Table 5. Here, the starting point of "depth" is the interface between the plated layer and the base steel sheet.
[0173] In addition, a sample cut into 25 mm × 15 mm was obtained and etched with nitric acid. The thickness of the layer in which the ferrite phase accounted for 90% or more was measured by the above method and is shown in the "α phase thickness" of Table 5. Here, the starting point of "thickness" is the interface between the coating layer and the base steel sheet.
[0174] In addition, the plating was removed using a 10 mass % hydrochloric acid solution to which 0.06 mass % inhibitor (IBIT manufactured by Asahi Chemical Industries, Ltd.) was added, and the roughness of the surface of the exposed steel sheet was measured in the same manner as before annealing, and is shown in the "Base Steel Sheet / Plating Interface Roughness" in Table 5.
[0175] (Tensile Strength Evaluation)
[0176] For each plated steel sheet, a JIS No. 5 tensile test piece was obtained with the direction perpendicular to the rolling direction as the longitudinal direction, and a tensile test was performed in accordance with JIS Z2241:2011 to obtain the tensile strength, which was evaluated as follows.
[0177] Rating AAA: 1180MPa or above
[0178] Evaluation AA: 980MPa or more and less than 1180MPa
[0179] Evaluation A: 780MPa or more and less than 980MPa
[0180] (Evaluation of LME resistance)
[0181] Two samples cut into a size of 50 mm × 100 mm were obtained from each steel plate. For the two samples, spot welding was performed using a dome radius welding electrode with a front end diameter of 8 mm at an angle of 2°, a pressure of 4.0 kN, a power-on time of 0.5 seconds and a power-on current of 12 kA to produce welded joints.
[0182] Reference Figure 2 , the evaluation of LME resistance is described. LME resistance is evaluated by the length of the LME crack (crack 11 at the shoulder) generated at the shoulder of the weld 2 formed by spot welding two steel plates 1 overlapped. The shoulder refers to the inclined portion of the edge of the recess generated by spot welding. According to the length of the crack 11 at the shoulder, the evaluation is as follows. In this embodiment, if the evaluation is A or above, it is judged that the LME resistance is excellent, and the problem to be solved by the present invention is solved.
[0183] Rating AAA: 0μm
[0184] Evaluation AA: greater than 0μm and less than 60μm
[0185] Evaluation A: 60 μm or more and less than 120 μm
[0186] Evaluation B: 120μm or more
[0187] (Red rust resistance evaluation)
[0188] A sample cut into a size of 75 mm × 100 mm was obtained from each plated steel sheet, and the end and back surfaces of the sample were protected with a tape seal. Then, a cross-cut cut was made to reach the plated layer, and a salt spray test of 5% NaCl maintained at 35°C was carried out in accordance with JIS Z2371:2015. The test was carried out until 2000 hours, and the time for red rust to occur after the test was calculated. Based on the time for red rust to occur, the evaluation was performed as follows. In this embodiment, if the evaluation is A or above, it is judged that the red rust resistance is excellent.
[0189] Rating AAA: Red rust generation time is more than 2000 hours
[0190] Evaluation AA: Red rust generation time is more than 1000 hours and less than 2000 hours
[0191] Evaluation A: Red rust generation time is more than 240 hours and less than 1000 hours
[0192] Evaluation B: Red rust generation time is less than 240 hours
[0193] Table 5 shows the results of each evaluation.
[0194] Table 5
[0195]
[0196] ※ The underlined elements are outside the scope of the present invention or the expected properties cannot be obtained.
[0197] No. 29 is a comparative example in which the C content of the steel plate is high. It is believed that since the C content of the steel plate is high, decarburization of the surface layer does not advance even through high dew point annealing. Therefore, the depth at which the C concentration is 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase reaches 90% or more do not increase. As a result, the result of poor LME resistance is obtained. In addition, red rust resistance is also poor.
[0198] No. 30 is a comparative example in which the Si content of the steel sheet is small. It is believed that since the Si content of the steel sheet is small, even if high dew point annealing is performed, decarburization of the surface layer does not advance and ferrite is not stabilized. Therefore, the depth at which the C concentration is 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase reaches 90% or more do not increase. As a result, the result of poor LME resistance is obtained. In addition, red rust resistance is also poor.
[0199] No. 31 is a comparative example in which the Si content and the sum of the Si and sol. Al contents of the steel sheet are small. It is considered that since the Si content and the sum of the Si and sol. Al contents of the steel sheet are small, even if high dew point annealing is performed, decarburization of the surface layer does not advance and ferrite is not stabilized. Therefore, the depth at which the C concentration is 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase reaches 90% or more do not increase. As a result, the result of poor LME resistance is obtained. In addition, red rust resistance is also poor.
[0200] No. 32 is a comparative example in which the Si content of the steel sheet is high. It is believed that since the Si content of the steel sheet is high, even if high dew point annealing is performed, external oxidation is advanced, and oxides (scale) are formed on the surface layer of the steel sheet, which inhibits decarburization on the outermost surface. Therefore, the depth at which the C concentration is 0.05% or less does not increase. As a result, the result is poor in LME resistance. In addition, red rust resistance is also poor.
[0201] No. 33 is a comparative example in which the sol. Al content of the steel sheet is small. It is believed that since the sol. Al content of the steel sheet is small, even if high dew point annealing is performed, decarburization of the surface layer does not advance and ferrite is not stabilized. Therefore, the depth at which the C concentration is 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase reaches 90% or more do not increase. As a result, the result of poor LME resistance is obtained. In addition, red rust resistance is also poor.
[0202] No. 34 is a comparative example in which the sol. Al content and the sum of the contents of Si and sol. Al of the steel sheet are small. It is considered that since the sol. Al content and the sum of the contents of Si and sol. Al of the steel sheet are small, even if high dew point annealing is performed, decarburization of the surface layer does not advance and ferrite is not stabilized. Therefore, the depth at which the C concentration is 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase reaches 90% or more do not increase. As a result, the result of poor LME resistance is obtained. In addition, red rust resistance is also poor.
[0203] No. 35 is a comparative example in which the sol. Al content of the steel sheet is high. It is believed that since the sol. Al content of the steel sheet is high, even if high dew point annealing is performed, external oxidation is advanced, and oxides (scale) are formed on the surface layer of the steel sheet, which inhibits decarburization on the outermost surface. Therefore, the depth at which the C concentration is 0.05% or less does not increase. As a result, the result is poor in LME resistance. In addition, red rust resistance is also poor.
[0204] No. 36 is a comparative example in which the sum of the Si and sol. Al contents of the steel sheet is small. It is considered that since the sum of the Si and sol. Al contents of the steel sheet is small, even if high dew point annealing is performed, decarburization of the surface layer does not advance and ferrite is not stabilized. Therefore, the depth at which the C concentration is 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase reaches 90% or more do not increase. As a result, the result of poor LME resistance is obtained. In addition, red rust resistance is also poor.
[0205] It is considered that since the dew point of No. 37 was low during annealing, a phase containing oxides of Si, Mn, Al, etc. was formed on the outside of the steel sheet during annealing, which hindered the mutual diffusion of the plating components and the steel components during the plating process. As a result, appropriate plating could not be obtained.
[0206] It is considered that since the dew point of No. 38 was high during annealing, a phase containing oxides of Si, Mn, Al, etc. was formed on the outside of the steel sheet during annealing, which hindered the mutual diffusion of the plating components and the steel components during the plating process. As a result, appropriate plating could not be obtained.
[0207] It is considered that in No. 39, the holding temperature during annealing was low, so decarburization was not sufficiently promoted during annealing. Therefore, the depth of the C concentration of 0.05% or less and the thickness of the layer where the area ratio of the ferrite phase reached 90% or more did not increase. As a result, the LME resistance was poor. In addition, the red rust resistance was also poor.
[0208] It is considered that in No. 40, since the holding temperature during annealing was high, decarburization was not sufficiently promoted during annealing. Therefore, the depth at which the C concentration was 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase was 90% or more did not increase. As a result, the LME resistance was poor. In addition, the red rust resistance was also poor.
[0209] It is considered that in No. 41, since the holding time during annealing was short, decarburization was not sufficiently promoted during annealing. Therefore, the depth at which the C concentration was 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase was 90% or more did not increase. As a result, the LME resistance was poor. In addition, the red rust resistance was also poor.
[0210] It is believed that since brushing in the pre-treatment process was not performed in No. 42, strain was not introduced into the surface of the steel sheet, and decarburization did not advance during annealing. Therefore, the depth at which the C concentration was 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase reached 90% or more did not increase. As a result, the LME resistance was poor. In addition, the red rust resistance was also poor.
[0211] It is believed that in No. 43, since a brush with a large grinding amount was used in the pre-treatment process, the roughness of the steel plate surface increased, and the ferrite phase was not stabilized. Therefore, the thickness of the layer with an area ratio of ferrite phase of 90% or more did not increase. As a result, the LME resistance was poor. In addition, the red rust resistance was also poor.
[0212] No. 1 to No. 28 are examples of the present invention, and have high LME resistance. In addition, they are also excellent in red rust resistance. It was confirmed that examples with a depth of 0.05% or less of C concentration and a large thickness of a layer with an area ratio of ferrite phase of 90% or more have particularly excellent LME resistance.
[0213] Industrial Applicability
[0214] According to the present invention, a plated steel sheet having high LME resistance can be provided, and the plated steel sheet can be suitably used for applications such as automobiles, home appliances, and building materials, and particularly for automobiles. Therefore, the present invention has extremely high industrial applicability.
[0215] Explanation of symbols
[0216] 1 Steel Plate
[0217] 2 Welding section
[0218] 11 Cracks in the shoulder
Claims
1. A plated steel sheet, characterized in that: The plated steel sheet has a Zn-containing plating layer on one or both surfaces of a base steel sheet and has a tensile strength of 780 MPa or more. Chemical composition by mass% contains: C:0.05~0.40%、 Si: 0.7-3.0%, Mn: 0.1-5.0%, Sol.Al: 0.7~2.0%, P: 0.0300% or less, S: 0.0300% or less, N: 0.0100% or less, B:0~0.010%、 Ti: 0~0.150%, Nb: 0~0.150%, V:0~0.150%、 Cr:0~2.00%、 Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W:0~1.00%、 Ca: 0~0.100%, Mg: 0~0.100%, Zr:0~0.100%、 Hf: 0~0.100%、 REM: 0~0.100%, The rest is Fe and impurities. The total content of Si and sol.Al is 1.8% or more. Taking the interface between the base steel sheet and the plated layer as the starting point, in the depth direction of the plated steel sheet, the depth at which the C concentration measured by GDS is 0.05% or less is 10 μm or more, Taking the interface between the base steel sheet and the plated layer as a starting point, in the depth direction of the plated steel sheet, a layer having an area ratio of ferrite phase of 90% or more has a thickness of 20 μm or more, The roughness of the interface between the base steel sheet and the coating layer is 3.0 μm or less in terms of Ra. The coating layer contains less than 3.0% Fe by mass, and the remainder is Zn and impurities.
2. The plated steel sheet according to claim 1, characterized in that: The roughness of the interface between the base steel sheet and the coating layer is 2.0 μm or less in terms of Ra.
3. The plated steel sheet according to claim 1, characterized in that Taking the interface between the base steel sheet and the plated layer as a starting point, the depth at which the C concentration measured by GDS is 0.05% or less in the depth direction of the plated steel sheet is 20 μm or more.
4. The plated steel sheet according to claim 1, characterized in that Starting from the interface between the base steel sheet and the plated layer, a layer having an area ratio of ferrite phase of 90% or more has a thickness of 30 μm or more in the depth direction of the plated steel sheet.
5. The plated steel sheet according to any one of claims 1 to 4, characterized in that: The plating layer contains, by mass%, Al: 0 to 30.0% and Mg: 0 to 10.0% in place of a portion of the Zn.
6. The plated steel sheet according to any one of claims 1 to 4, characterized in that: The plating layer contains, by mass%, Al: 10.0 to 30.0% and Mg: 4.5 to 10.0% in place of a portion of the Zn.
Citation Information
Patent Citations
Steel sheet, hot-dip zinc-coated steel sheet, and alloyed hot-dip zinc-coated steel sheet
WO2019116531A1
Steel sheet
WO2020218575A1